2016
DOI: 10.1186/s12890-016-0222-4
|View full text |Cite
|
Sign up to set email alerts
|

Practice and knowledge about diagnosis and treatment of alpha-1 antitrypsin deficiency in Spain and Portugal

Abstract: BackgroundDetermining physicians’ awareness about alpha-1 antitrypsin (AAT) deficiency (AATD) may help to explain the discrepancy between the observed and expected number of patients diagnosed with this disease.This study was designed to assess the opinions on knowledge, practice pattern and attitude regarding AATD among physicians in Spain and Portugal.MethodsAn online anonymous survey was performed on pulmonologists (n = 100), internal medicine specialists (IMS) (n = 100) and primary care physicians (PCP) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
(34 reference statements)
2
22
0
1
Order By: Relevance
“…National and international guidelines recommend that all patients with COPD, non-reversible asthma and unexplained liver disease should be tested for AATD [4,12,70,71]. Despite these recommendations, identification of AATD remains low due to a continued lack of disease awareness and poor adherence to testing recommendations [72,73]. It has been suggested that this reflects the erroneous perception of high costs associated with testing [12,72].…”
Section: Identifying Pi*sz Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…National and international guidelines recommend that all patients with COPD, non-reversible asthma and unexplained liver disease should be tested for AATD [4,12,70,71]. Despite these recommendations, identification of AATD remains low due to a continued lack of disease awareness and poor adherence to testing recommendations [72,73]. It has been suggested that this reflects the erroneous perception of high costs associated with testing [12,72].…”
Section: Identifying Pi*sz Individualsmentioning
confidence: 99%
“…Despite these recommendations, identification of AATD remains low due to a continued lack of disease awareness and poor adherence to testing recommendations [72,73]. It has been suggested that this reflects the erroneous perception of high costs associated with testing [12,72]. Measures such as the cost-effective detection programme set up by the Spanish Registry of Patients with AATD may help to alleviate this concern and improve diagnosis [72].…”
Section: Identifying Pi*sz Individualsmentioning
confidence: 99%
“…There is evidence to suggest that primary care physicians in particular have low awareness/knowledge of AATD, and do not always follow fundamental recommendations such as testing all newly diagnosed COPD patients for AATD. 13 Underpinning this issue is continued low awareness of the disease, and this is an area that ERN-LUNG and EARCO will endeavor to address through raising the profile of AATD and by connecting specialist and non-specialist physicians.…”
Section: Standardization and Reliability Of Aatd Diagnosticsmentioning
confidence: 99%
“…12 This may result from reluctance of the patient to seek medical attention, lack of health care practitioner awareness, and failure to conduct AATD testing when warranted. 5,[13][14][15][16] A recent study from the United Kingdom (UK) found that only~2% of COPD patients diagnosed at <60 years had undergone any form of AATD testing. 16 Because of this, efforts to increase disease awareness and testing rates are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Although AAT deficiency is the most common hereditary disease diagnosed in adults, there is a generalized lack of knowledge in the medical community about this disorder [10,11]. Many physicians are not aware that pulmonary conditions, such as chronic obstructive pulmonary disease or liver disease may actually be due to AATD [11]. Panniculitis is another clinical manifestation of AATD and may also be significantly underdiagnosed [4].…”
Section: Introductionmentioning
confidence: 99%